Lexicostatistics Calculation on Manggarai and Bima Languages: A Comparative Historical Linguistics Study - Salahuddin, Salahuddin (PAROLE: Journal of Linguistics and Education, 2023)
This study aims to provide quantitative and qualitative evidence through lexicostatistical calculations to determine the separation distance and possible relationship between the Manggarai and Bima languages. Manggarai and Bima languages are two Austronesian languages belonging to the Central-Eastern-Malayo-Polynesian located on two adjacent islands. Manggarai is the language spoken by the Manggarai tribe on West Flores Island, while the Bima is the language spoken on the island of Sumbawa. This is based on evidence of the discovery of several vocabularies that have similar forms and meanings in both languages. The researcher uses secondary data provided in Lexirumah and Austronesian Basic Vocabulary databases that contain Austronesian lexical data based on 200 Swadesh word lists promoted by Swadesh (1952). Based on lexicostatistical calculations, the results show that the two languages show a kinship level of 27%, which means that the Manggarai and Bima languages are two different languages from different family group (stock level), or, in other words, the Bima and Manggarai languages were a single language 3.016±242 years ago. Meanwhile, the qualitative results were obtained by considering the related vocabulary between the two languages and showing the existence of sound correspondences, such as [w]~[v], [f]~[p], [d]~[t], [r]~[l], and [a]~ [e].